Analysis of Low-Speed Diesel Engine Connecting Rod Made of AL360. Issue 1 (May 2021) - Helal, Wasim M. K.; Wenping, Zhang; Xiaobo, Li; Guixin, Wang; Yanpan, Su; guangku, Chen
Abstract: Connecting rod is one of the most important and critical components in an engine. The scientists should work on it in order to improve its performance. In the current study, in order to analyse the stress and deformation surrounding the connecting rod, the 3 D model is built. A connecting rod made of AL360 is investigated in this study. Stress distribution and deformation of a con-rod made of AL360 are carried out.